A Retrospective Study of Brain-Heart Syndrome in Patients with Acute Cerebrovascular Diseases - Tang H; Xing X; Han Y; Gao D; Chan P; Zhang S; Xue H (Risk Management and Healthcare Policy, 2024)
Hui Tang,1 Xiurong Xing,1 Yingna Han,1 Daiquan Gao,2 Piu Chan,3 Shengfang Zhang,4 Huixin Xue4 1Department of Emergency Internal Medicine, Xuanwu Hospital of China Capital Medical University, Beijing, People’s Republic of China; 2Department of Neurology, Xuanwu Hospital of China Capital Medical University, Beijing, People’s Republic of China; 3Department of Neurobiology, Xuanwu Hospital of China Capital Medical University, Beijing, People’s Republic of China; 4School of Medicine, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Hui Tang, Department of Emergency Internal Medicine, Xuanwu Hospital of China Capital Medical University, No. 45 of Changchun Street, Xicheng District, Beijing, 100053, People’s Republic of China, Tel +86-1083198280, Email tanghui_202186@21cn.comObjective: To investigate the clinical characteristics, risk factors and outcomes of brain-heart syndrome (BHS) in patients with acute cerebrovascular diseases (ACVDs).Methods: A retrospective analysis was conducted of 100 patients who were admitted to our hospital with ACVDs between January 2023 and December 2023. The demographic, clinical, laboratory and imaging data of the patients were collected, and the presence and severity of BHS were evaluated. The neurological and cardiac outcomes of the patients at discharge and at 12-month follow-up were also assessed.Results: Out of the 100 patients, 38% had BHS, classified as mild (18%), moderate (12%) and severe (8%). The most prevalent ACVDs were cerebral infarction (58%), cerebral haemorrhage (32%) and subarachnoid haemorrhage (10%). Cardiac complications included arrhythmia (26%), myocardial ischaemia (18%) and heart failure (10%). Patients with BHS had higher results for blood pressure, heart rate, white blood cell count, C-reactive protein, IL-6, D-dimer and troponin, more severe neurological deficits, higher mortality and poorer functional outcomes. Multivariable analysis identified age, hypertension, diabetes, coronary artery disease, prior cardiovascular events, cerebral haemorrhage, brainstem infarction and hypothalamic or insular lesions as independent risk factors for BHS.Conclusion: Brain-heart syndrome is a frequent, severe complication in patients with ACVD, linked with multiple risk factors and poor prognosis. Prompt diagnosis and treatment are crucial for improving patient outcomes.Keywords: brain-heart syndrome, acute cerebrovascular diseases, cerebral infarction, cerebral haemorrhage